Juridical Analysis of the Flexibility in Procurement Procedures For Goods and Services During the Covid-19 Emergency Period From the Perspective of Administrative Law and the Risk of Abuse of Authority - Sekali, Gidion Karo; Setiono, Joko; Rudhanto, Albertus Wahyu (Greenation Publisher & Yayasan Global Resarch National, 2025)
The COVID-19 pandemic prompted the government to take swift action in meeting public needs through emergency procurement of goods and services. In such situations, procurement procedures do not follow standard mechanisms, but instead are granted flexibility specifically regulated through instruments such as Presidential Regulation Number 16 of 2018 in conjunction with Presidential Regulation Number 12 of 2021, as well as LKPP Regulation Number 13 of 2018. This study aims to analyze the legality of such procedural flexibility during emergencies from the perspective of administrative law and to examine the potential for abuse of authority that may arise. A normative juridical approach is used to examine the relevance of general principles of good governance (AUPB), such as proportionality, accountability, and transparency, as stipulated in Law Number 30 of 2014 on Government Administration. The analysis reveals that while procedural flexibility in emergency situations is normatively justified, weaknesses in oversight and limited technical guidance open opportunities for irregularities, such as mark-up practices, direct appointments without real needs, and conflicts of interest. The absence of clear limits on discretionary power also poses a risk of abuse of power. Therefore, there is a need to strengthen regulations, enhance the capacity of procurement personnel, and optimize risk-based oversight technologies to ensure accountability at every stage of emergency procurement. This study is expected to contribute to the formulation of more adaptive procurement policies that remain grounded in the principles of administrative law, ensuring justice and legal certainty.